Islam - "Guillaume, Alfred" ("Middlesex, Eng.", 1982)
The cultural background of the Arab Peoples, who are playing an ever larger and larger part in the modern world, has been formed as much by a great missionary religion, Muhammadanism, as has that of Europe and America by Christianity. The great awakening of the Musliim world which is now in progress, the emergence of new Muslim states such as Pakistan, Libya, Jordon, Saudi Arabia, and the ever closer contact between the West and Middle East makes an understanding of the spirit of Islam essential to the informed Westerner. Professor Guillaume provides the essentials for such an Understanding in this book. He deals in turn with Muhammad, the founder of Islam: the Quran, its holy book; the evolution of Muhammandanism as a system of faith, law, religion, and philosophy; the varying schools of thought and the intense devotional life that have grown up within.
Keywords: Islam